Revisiting car dependency: A worldwide analysis of car travel in global metropolitan areas. (January 2022) - Saeidizand, Pedram; Fransen, Koos; Boussauw, Kobe
Abstract: This article aims to contribute to the understanding of car dependency of cities, a line of inquiry which emerged in the late 1980s. First, we update possibly outdated insights based on more recent data. Second, we highlight methodological limitations of this type of research, which will help determine the relevance of typical findings in the broader debate on urban sustainability. For our analysis, we base ourselves on the Mobility in Cities Database which includes properties of urban form and mobility of 56 metropolitan areas worldwide. Using OLS modelling, we found that density, public transport supply and demand, car ownership, fuel price and level of congestion are important predictors of car use. However, although these variables are significantly associated with car travel in metropolitan areas, they do explain variance to a limited extent only, partly since such variables do not cover underlying personal attributes such as age, income, attitudes, or residential self-selection. This puts the findings and the implications of earlier comparative analysis of car dependency of metropolitan areas into perspective and questions the tendency of urban planning policies to view urban density as a silver bullet solution. Highlights: Density has limited impact on car dependency in global metropolitan areas. Public transport and transport economics variables enhance the influence of density. A 'car modal share' based model is more powerful than a 'VKT per capita' based model. Widely adopted outcomes of previous research could be treated more cautiously.